Enzymatic Extraction and Modification, and Frying Stability of Moringa Oleifera Seed Oil. - Mohammed, Abdulkarim Sabo (2006)
Consumption of edible oils has grown with the increase in world population. The increasing health awareness and consciousness amongst consumers made the food industry more discriminating in the types of oil they use for food applications. Many circumstances have focused attention on high-oleic vegetable oils, which have been demonstrated to reduce the risk of coronary heart disease. The demand for high-oleic oils is increasing but there are only a few known sources available. Moringa oleifera seed oil, which is naturally high-oleic oil, therefore, presents a great opportunity for the oil industry for meeting this ever-increasing demand. The objectives of this study were to determine the properties of oil extracted from Moringa oleifera seeds, evaluate the efficiency of enzymatic-extraction of the oil and modification of the oil to enhance its oleic acid content and compare the oxidative stability of the oil against several other oils during deep fat frying.The oil content of M. oleifera seeds in Malaysia ranged between 30.8% and 33.4% depending on the variety, of which there were two. The physico-chemical properties of the oil were determined following extraction with light petroleum ether. The dominant fatty acid (FA) of the oil was indeed oleic acid, where Variety 1 contained 67.9% while Variety 2 contained 74.4%. After refining, the oil from both varieties is light golden color (O.1R + 1 .OY), and a viscosity, smoke point and refractive index (nD400C) of Cp 51.7, 206"C, and 1.4533, respectively. Using electronic nose analysis, the crude oil was found to have an odor similar to that of peanut oil. It has a complete melting point of 18.9"C. The crude oil contains 95.6% triacylglycerols (TAG) and 1.9% 1,2- and 1,3- diacylglycerols. The relative TAG content increased to 98.7% after refining. The oil contains 36.7% trioleoyl glycerol (000) as the main TAG. M. oleifera seed oil was extracted using four different types of enzymes namely; Neutrase 0.8L (neutral protease), Termamyl 120L, type L (a-amylase), Pectinex Ultra SP-L (pectinase) and Celluclast 1.5L FG (cellulase) all supplied by Novozymes (Bagsvaerd Denmark). The enzymes were used either separately or in combination. The efficiency of enzyme-extraction was compared to aqueous extraction without enzyme. Enzymatic-extraction of M. oleifera seed oil showed that Neutrase alone at 2% vlw, 45°C and pH 6.8 was able to extract 71.9% oil relative to the amount obtained when the oil was solvent-extracted. Neutrase was the most efficient among the enzymes used followed by Termamyl, Celluclast and Pectinex with percent oil recoveries of 64.8%, 62.6% and 56.5%, respectively. Each extraction was carried out at the optimum pH and temperature of the enzymes. A combination of the four enzymes at pH 7.5 increased the oil recovery to 74%. Percent oil recovery with all enzymes was significantly (P<0.05) higher than the control (aqueous extraction without enzyme) (3 5.6%). Solvent extracted M oleifera seed oil was transesterified using immobilized lipase (Lipozyme IM 60) (Novozyrnes Bagsvaerd Denmark) in order to change its melting and crystallizing behavior that will make it easier to fractionate. After transesterification, the oil was fractionated with acetone at -18°C and without acetone at 10°C to obtain two fractions, stearin and olein fractions. Incubation of the transesterified oil at 10°C for 24 h resulted in the formation of fat crystals, which settled at the bottom of the flask in sample transesterified for 24 h, while the control (0 h) sample became rather viscous with fat crystals in suspension. Transesterification affect the TAG profile of the oil, which in turn affected the solid fat content (SFC) and thermal behavior. The SFC value at 0°C after 24 h of reaction was 10.35% and significantly (P<0.05) higher than the control (0 h) (7.94%). The oil remained liquid at 20°C for all reaction times. The end set temperature (melting point) shifted from 18.9"C for the unreacted oil to 20S°C for oil transesterified for 24 h. Transesterification of the oil resulted also in a significant (P<0.05) increase in the crystallization temperature of the high melting glyceride from the original value of 1.6"C to 12.9"C after transesterification for 24 h. There was a significant increase in the oleic acid content in the olein fractions obtained following fractionation of the transesterified oil with and without using acetone (75.2 and 70.5%, respectively) compared to the unreacted oil (67.9%).The oxidative stability of refined M oleifera seed oil (MOO) in deep fat frying was evaluated and compared with canola (CLO), soybean (SBO), and palm olein (PO). The oils were used to fry potato chips for 6 h a day up to a maximum of 5 days. Changes in fatty acid (FA) composition, free fatty acids (FFA), iodine value (IV) peroxide value (PV), p-anisidine value (p-AV), specific extincti o;:1~n( 233 and 269 nm for conjugated dienes and trienes), total polar compounds (TPC), color and viscosities were used to evaluate the oils. The frying process caused an increase in the FFA contents MOO, PO, CLO and SBO. The FFA contents at the end of the frying period were 0.35%, 0.55%, 0.54% and 0.51% for CLO, PO, SBO and MOO, respectively. The rate of increase in the PV (meqOz/kg) for CLO (2.33 per day) was higher compared to those of MOO (0.80 per day), PO (1.00 per day), and SBO (0.70 per day). Conjugated dienes levels at the end of the frying period were lowest in PO (4.27) followed by MOO (6.07) with high levels in CLO (9.28) and SBO (10.64). The amount of TPC in MOO (20.78%) and PO (21.23%) were significantly (P<0.05) lower than those in CLO (28.73%) and SBO (3 1.82%). Color and viscosity of the oils increased with frying time. The rates of change of viscosity with the frying days were similar for all the oils. Results of sensory analysis conducted on potato chips fried in PO and MOO showed general acceptability of potato chips fried in both oils with high scores for crispness (7.07 and 7.14), oiliness (6.86 and 7.09), and fried food flavor (7.00 and 6.79) attributes, respectively. The overall acceptance of the French fries fried in MOO was high (7.50) and not significantly (P>0.05) from that of PO (7.58).